2014
DOI: 10.1111/ijcp.12459
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and the increased risk of pulmonary tuberculosis: a population-based case-control study

Abstract: Long-term ICS use may increase the risk of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
19
1
1
Order By: Relevance
“…Overall ICS use caused a 2.04‐fold increased risk of developing TB. Interestingly, it appeared from this study that high doses of ICS place the patient at a risk level (OR 2.32) similar to that found in those receiving disease modifying anti‐rheumatic drugs such as anti‐TNFα . Chung's study actually confirms another recent cohort study conducted in South Korea from a large database of the Health Insurance Review and Assessment Service although the risk was somewhat lower in the latter with an odd ratio for TB diagnosis of 1.2 in those receiving ICS whichever the underlying obstructive disease .…”
supporting
confidence: 77%
“…Overall ICS use caused a 2.04‐fold increased risk of developing TB. Interestingly, it appeared from this study that high doses of ICS place the patient at a risk level (OR 2.32) similar to that found in those receiving disease modifying anti‐rheumatic drugs such as anti‐TNFα . Chung's study actually confirms another recent cohort study conducted in South Korea from a large database of the Health Insurance Review and Assessment Service although the risk was somewhat lower in the latter with an odd ratio for TB diagnosis of 1.2 in those receiving ICS whichever the underlying obstructive disease .…”
supporting
confidence: 77%
“…The International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM), was used for the diagnosis codes. The reliability of epidemiologic studies used in LHID2000 has been reported in our previous studies …”
Section: Methodsmentioning
confidence: 99%
“…The reliability of epidemiologic studies used in LHID2000 has been reported in our previous studies. 21,22…”
Section: Data Sourcementioning
confidence: 99%
“…In terms of side-effects, a greater increase in the risk of pneumonia related to ICS was found in current smokers, and patients with prior pneumonia, body mass index <25 kg/m 2 and severe airflow limitation (51). Beyond intrinsic patients’ characteristics, environmental factors may also influence the benefit-risk ratio of ICS, as recently suggested for the ICS-associated risk of tuberculosis, which is greater in countries with high incidence of tuberculosis (52). …”
Section: Positioning Current Therapeutic Options – the Gold (R)evolutionmentioning
confidence: 99%